The control volume radial basis function method CV-RBF with Richardson extrapolation in geochemical problems. (March 2015) - Florez, W.F.; Portapila, M.; Hill, A.F.; Power, H.; Orsini, P.; Bustamante, C.A.
Abstract: The aim of this paper is to present how to implement a control volume approach improved by Hermite radial basis functions (CV-RBF) for geochemical problems. A multi-step strategy based on Richardson extrapolation is proposed as an alternative to the conventional dual step sequential non-iterative approach (SNIA) for coupling the transport equations with the chemical model. Additionally, this paper illustrates how to use PHREEQC to add geochemical reaction capabilities to CV-RBF transport methods. Several problems with different degrees of complexity were solved including cases of cation exchange, dissolution, dissociation, equilibrium and kinetics at different rates for mineral species. The results show that the solution and strategies presented here are effective and in good agreement with other methods presented in the literature for the same cases. Abstract : Highlights: A control volume Hermite RBF scheme has been implemented for groundwater reactive problems. The standard SNIA approach was improved by a Richardson extrapolation. The PHREEQ modules are coupled with a transport solution by a local RBF method. The solution by CV-RBF is effective and in agreement with other numerical methods.